3D hierarchical defect-rich C@MoS2 nanosheet arrays developed on montmorillonite with enhanced performance in Pb(ii) removal. Issue 10 (3rd September 2020) - Tan, Lin; Liu, Yunsong; Meng, Fanling; Wu, Pengfei; Xia, Yunxue; Tang, Yuanyuan
Abstract : A novel C@MoS2/MMT composite was prepared with 3D hierarchical superstructures for selective Pb(ii ) removal, with ∼95% of Pb(ii ) ions adsorbed in the presence of various competing ions. Abstract : As an emerging material for environmental remediation, MoS2 with various dimensional nanostructures has attracted much attention. Herein, a novel C@MoS2 /montmorillonite composite material (C@MoS2 /MMT) with 3D hierarchical superstructures was successfully prepared via the facile one-step solvothermal growth of MoS2 nanosheets with the assistance of glucose on the surface of montmorillonite (MMT). The structural analysis indicated the formation of a 3D C@MoS2 /MMT composite with C and defect-abundant MoS2 embedded on the MMT surface with the presence of amidogen and hydroxyl groups. Consequently, the C@MoS2 /MMT composite was subjected for the removal of Pb(ii ) in aquatic systems and attained a maximum adsorption capacity of 187.0 mg g −1 at 298 K. Additionally, the composite was found to have very high selectivity to Pb(ii ); it can effectively adsorb approximately 95% of Pb(ii ) ions in the presence of various competing ions (Cu(ii ), Zn(ii ), Cd(ii ) and Cr(vi )). Furthermore, the structural and morphological characteristics and possible removal mechanisms were intensively explicated in this work. The mechanism study indicated that the enhanced Pb(ii ) removal was due to electrostatic interactions, surface diffusion and the formation of PbMoO4 on the surface of C@MoS2 /MMT. Therefore, this work provides a strategy for efficient environmental remediation to design hybrid nanosheets with diverse heterogeneous 3D structures using earth-abundant transition metal dichalcogenide materials and natural clay minerals.